PELATIHAN DAN PENDAMPINGAN PENGGUNAAN TEKNOLOGI INFORMASI UNTUK PENINGKATAN KAPASITAS PRAJURU DESA ADAT DI BALI - Ni Wayan Wardani; I Putu Agus Eka Darma Udayana; Komang Redy Winatha; I Putu Yoga Indrawan; Putu Gede Surya Cipta Nugraha; Eddy Hartono; I Nyoman Agus Suarya Putra; Ni Made Mila Rosa Desmayani (Sewagati, 2023)
A traditional village in Bali is an institution that is responsible for managing and maintaining the sustainability of a traditional village in Bali. The development of information technology has developed so rapidly that even village officials must keep up with the development of information technology. However, in reality some village officials are not fluent in using information technology either in the form of Microsoft Word, Excel, Power Point, especially now that online meetings are also developing with many positive impacts. Based on these problems, community service was carried out by conducting Microsoft Word, Excel, Power Point training, and online meetings using the Zoom application. This training was conducted with the aim of increasing the skills of indigenous village communities in using information and communication technology. In this training, participants will be taught how to use Microsoft Word, Excel, and Power Point to create documents, process data, and make presentations. In addition, participants will also be taught how to use the Zoom application to conduct online meetings. This training is expected to provide benefits for indigenous village communities in improving their skills and productivity. Based on the evaluation results that have been carried out using the pre-test and post-test methods, in general there is an increase in the ability of village officials to operate the information technology material that has been provided in this community service.